Nagorno-Karabakh and the Armenian Question: A Legal Conundrum - Marsili, M. (European Consortium for Political Research General Conference 2021 (ECPR General Conference 2021), 2021)
The Nagorno-Karabakh conflict involves a set of questions and interests that make it hard to be solved within the framework of current international law. Reportedly, in this long-lasting conflict there were serious violations of international law and international humanitarian law; all parties involved accused each other of war crimes and eventually resorted to the European Court of Human Rights. So far, for such alleged violations, no legal remedy was possible under the current international legal framework, just as there are many issues still on the table relating to the Armenian question. The Law of Nations is – or should be – the set of rules for the international community. Customary and treaty law are the legal means aimed to resolve and prevent disputes between states; they should serve to overcome the law of the jungle. This paper is aimed to scrutinize the legal conundrum of the Nagorno-Karabakh conflict by investigating it within the overall context of the Armenian question.